1968
DOI: 10.1139/o68-010
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin sulfate changes in puppy rib cartilage during the period of calcification

Abstract: B O~B S S , J. M., and S~e m , M. Chohdroitin sulfate changes Im puppy rib cartilage during the period of calcification. Can. 9. Bimkm. 46, 63 (1968).Using a single litter of seven puppies, it was found that in the period (1'3-30 weeks of age) when calcification was occurring in most of the ribs there was a change in the extractability of the chondroitin sulfate in this tissue. There was a decrease in the amount of chondroith sulfate which could be extracted by homogenizing with water and an increase in the am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1969
1969
1977
1977

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The sum of the measured constituents in the dry fat-free solids of the epiphyses of the bones of the malnourished children was therefore lower than the corresponding value for the bones of the control children. It is possible that the difference was caused by a higher concentration of mucopolysaccharides in the less highly calcified epiphyses of the malnourished children, for Bowness & Jacobs (1968) have shown that the concentration of chondroitin sulphates in the rib falls during calcification.…”
Section: Composition Of the Non-epiphyseal Parts Of The Femurmentioning
confidence: 99%
“…The sum of the measured constituents in the dry fat-free solids of the epiphyses of the bones of the malnourished children was therefore lower than the corresponding value for the bones of the control children. It is possible that the difference was caused by a higher concentration of mucopolysaccharides in the less highly calcified epiphyses of the malnourished children, for Bowness & Jacobs (1968) have shown that the concentration of chondroitin sulphates in the rib falls during calcification.…”
Section: Composition Of the Non-epiphyseal Parts Of The Femurmentioning
confidence: 99%